NMR thermometry of vanadium based ligand-to-metal-charge transfer complexes - Grundy, Josef, author; Zadrozny, Joe, advisor; Crans, Debbie, advisor; Wu, Mingzhong, committee member (Colorado State University. Libraries, 2023)
Magnetic resonance imaging (MRI) is a noninvasive imaging technique that utilizes safe, nonionizing radiation for the diagnosis of early-stage diseases, including cancer. Although this technique provides a wealth of anatomical information, there are limitations in the information that MRI provides, such as the accurate local temperature in specific parts of the body. 51V is a promising candidate for a high-resolution NMR thermometer due to its intrinsically low quadrupolar moment and subsequent narrow linewidth. Unlike other nuclei, such as 59Co, design strategies for increasing the temperature sensitivity of 51V complexes are currently unexplored. We present a route of amplifying temperature sensitivity of the 51V chemical shift via ligand-to-metal charge transfer electronic structure design criteria. We demonstrate that this design strategy can boost the temperature dependence of the 51V chemical shift by an order of magnitude.
Keywords: linewidth; NMR; vanadium; LMCT; 51V-NMR; thermometry